Mechanisms used by plant growth-promoting rhizobacteria to boost plant growth - a Review - Amirul H., Muhammad Umar; Ab. Aziz, Zakry Fitri; A. Rahman, Mohammad Fitri; Mohammad Sazali, Muhammad I. N. H.; Kundat, Franklin Ragai; Masnindah, Malahubban; Mohammad Yusoff, Martini (TathQeef Scientific Publishing, 2023)
Several decades after the green revolution, the agricultural industry depended on artificial chemical fertilisers to achieve higher crop yields. This practice, however, contributes to a hazardous impact on the farming ecosystem, causing a smaller deposit of arable land for crop cultivation and production worldwide. Since the 2000s, people, industries, and governments are aware that it is time for everyone to shift to new technology which promotes responsible land use for agriculture. One of the technologies is plant growth-promoting rhizobacteria to enhance crop productivity and potentially rehabilitate soil health directly or indirectly. This review paper outlines the mechanisms used by plant growth-promoting rhizobacteria to promote plant growth. The tools could be opening up new ideas to address one of the recent and urgent world agriculture issues, food security.